Optimum Design and Control of a Quick-Return Mechanism Used in a Jewelry Welding Powder Production Machine - Yiğid, Osman; Şen, Murat (Hibetullah KILIÇ, 2023)
Quick-return mechanism Sliding mode control Jewelry welding powder Optimum design
Keywords: Mechanical Engineering; Makine Mühendisliği